Effects of warming and elevated O3 concentrations on N2O emission and soil nitrification and denitrification rates in a wheat-soybean rotation cropland. (February 2020) - Wang, Yuanyuan; Hu, Zhenghua; Shang, Dongyao; Xue, Ying; Islam, A.R.M. Towfiqul; Chen, Shutao
Abstract: The effects of warming and elevated ozone (O3 ) concentrations on nitrous oxide (N2 O) emission from cropland has received increasing attention; however, the small number of studies on this topic impedes understanding. A field experiment was performed to explore the role of warming and elevated O3 concentrations on N2 O emission from wheat-soybean rotation cropland from 2012 to 2013 using open-top chambers (OTCs). Experimental treatments included ambient temperature (control), elevated temperature (+2 °C), elevated O3 (100 ppb), and combined elevated temperature (+2 °C) and O3 (100 ppb). Results demonstrate that warming significantly increased the accumulative amount of N2 O ( AAN ) emitted from the soil-winter wheat system due to enhanced nitrification rates in the wheat farmland and nitrate reductase activity in wheat leaves. However, elevated O3 concentrations significantly decreased AAN emission from the soil-soybean system owing to reduced nitrification rates in the soybean farmland. The combined treatment of warming and elevated O3 inhibited the emission of N2 O from the soybean farmland. Additionally, both the warming and combined treatments significantly increased soil nitrification rates in winter wheat and soybean croplands and decreased denitrification rates in the winter wheat cropping system. Our results suggest that global warming and elevated O3 concentrations will strongly affect N2 O emission from wheat-soybean rotation croplands. Graphical abstract: Image 1 Highlights: Artificial warming increased N2 O emission while elevated O3 reduced it. Artificial warming and elevated O3 both increased soil nitrification rates. Artificial warming and elevated O3 both decreased soil denitrification rates. Warming and elevated O3 have combined effects on the soil N cycle. Abstract : Warming increased N2 O emission from wheat-soybean rotational cropland, whereas elevated O3 decreased N2 O emission.